2003
DOI: 10.1007/s00403-003-0411-x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of catechin against the superantigen staphylococcal enterotoxin B (SEB)

Abstract: Staphylococcal superantigens (SsAgs) have gained attention as one of the factors aggravating atopic dermatitis (AD) and several potential mechanisms of AD aggravation by SsAgs have been reported. Tea catechin has been found to have many unique antimicrobiological activities such as antibacterial, antiviral, antifungal and antitoxic effects. In the present study, we investigated the inhibitory effect of the green tea catechin extract, Polyphenon, and (-)-epigallocatechin gallate (EGCg) on staphylococcal enterot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 29 publications
0
23
0
1
Order By: Relevance
“…Some of these molecules act by precipitating the targeted toxin from solution (Choi et al , 2007; Hisano et al , 2003; Verhelst et al , 2013). We found that Draq5 inhibits toxin activity by directly modifying membrane structure, a finding that is similar to a previously reported finding that resveratrol inhibits cholera toxin (CT) activity by disrupting internalization of the toxin but not binding to the cell membrane (Morinaga et al , 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Some of these molecules act by precipitating the targeted toxin from solution (Choi et al , 2007; Hisano et al , 2003; Verhelst et al , 2013). We found that Draq5 inhibits toxin activity by directly modifying membrane structure, a finding that is similar to a previously reported finding that resveratrol inhibits cholera toxin (CT) activity by disrupting internalization of the toxin but not binding to the cell membrane (Morinaga et al , 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been a number of studies on the antitoxic effects of catechins [31][32][33][34][35], only a few studies of Fig. 2 Final body weight of mice.…”
Section: Discussionmentioning
confidence: 99%
“…In experiments using Bagg albino (BALB/c) mice and human PBMCs another interesting antibacterial effect of EGCG was demonstrated, polyphenon, consisting of 50% EGCG, neutralized staphylococcal enterotoxin B in a dose- and incubation time-dependent manner by binding to enterotoxin B molecules (Hisano et al, 2003). Further work is needed to determine the effects of EGCG against different enterotoxins, and whether EGCG has neutralization properties against other staphylococcal superantigens such as toxic shock syndrome toxin.…”
Section: Egcg Against Staphylococcimentioning
confidence: 99%